Studi Literatur Hukum Hybrid Contract Di Lembaga Keuangan Syariah Dari Berbagai Perspektif - Mai Simahatie; Andri Soemitra (-, 2022)
This study aims to find out the hybrid contract law in Islamic financial institutions from various perspectives. The methodology of this study is a qualitative research design with a literature review research design and using a publish or perish application to collect articles. The results show that from 2017 to 2021 several studies related to hybrid contract law have been carried out from various perspectives, including 1. Hybrid contracts based on the maqhosid al-Shari'ah perspective, 2. Hybrid contracts based on the hadith perspective, 3. Hybrid contracts based on the scholars' perspective four madzhab, 4. Hybrid contracts are based on the perspective of fiqh muamalah, and from each of these points of view convey views on the halalness of hybrid contracts.